The Role of Content Marketing in Building the Branding of the Mayor of Baubau During the Nomination Period - Ardiansah Putra, Muhammad Rizal; Nurfida, Wa; Hastuti, Hastuti (Jogjakarta Communication Conference (JCC), 2025)
In the digital age, content marketing has emerged as an efficient strategy for brand development, particularly for local leaders such as the mayor of Baubau. This study examines the impact of content marketing on the branding of the mayor of Baubau throughout the candidacy phase. Data was gathered via interviews and social media content analysis, employing a qualitative methodology and case study framework. The study's results indicate that content marketing has effectively cultivated a favorable perception of the mayor of Baubau as a leader who is kind, approachable, inclusive, and with a clear vision. Campaign videos and motivational storylines have proven effective in increasing community engagement and strengthening brand identity. However, the challenge lies in preserving message consistency and handling communication crises. The results of this study indicate that content marketing is crucial for garnering voter support .